PENGARUH SISTEM PERPAJAKAN, KEADILAN PERPAJAKAN, RELIGIUSITAS PAJAK DAN SANSKI PAJAK TERHADAP PERSEPSI PENGGELAPAN PAJAK DI KABUPATEN KARAWANG - Syamsiah, Siti Syarah; Lukita, Carolyn; Sujaya, Fista Apriani (Sekolah Menengah Kejuruan (SMK) Pustek, 2024)
Despite a steady rise in oil and gas tax revenues and other sources of assistance, the actualization of tax income during the last five years has fallen short of the targeted amount. This study aims to examine how people see tax avoidance and how it relates to issues such as religious adherence, penalties, tax justice, and the tax system. This study used primary data and quantitative techniques. Twenty-31,471 individual taxpayers who were enrolled with the Pratama Karawang Tax Service Office (KPP) made up the sample for this study. One hundred individuals were polled by this method of purposive sampling. We used SmartPLS version 4.0 to evaluate the data collected from questionnaires. These results suggest that the tax system, tax justice, and tax penalties are some of the elements that impact people's opinions on tax evasion. Religious beliefs on taxes have little impact on how people perceive tax avoidance.